Business Process Improvement in Commercial Ship Division of PT. X: A Theory of Constraints Thinking Process Approach - Utario Esna Putra; Budisantoso Wirjodirdjo (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2013)
PT. X as one of the biggest shipyard is facing a great challenge to keep its existence. One of its division which has the largest production capacity and expected contribution, is Commercial Ship Division. At 2011 it only fulfilled 23,1% of its target, which brought a huge loss to the corporate. That condition presses Commercial Ship Division to manage a continuous improvement in business process. Facing a constrained resources, all effort must be effectively and efficiently carried on. In this research, solution in business process improvement is approached using Theory of Constraints Thinking Process. From Current Reality Tree (CRT) diagram, the model of problem is acquired. Future Reality Tree (FRT) diagram is used to depict how injection influence the improvement. Transition Tree (TT) is assembled to arrange the necessary step for improvement or a road map.